A dynamic impedance matching algorithm of three-stub tuners based on equivalent circuit analysis. Issue 4 (15th December 2020) - Lai, Shimiao; Qiao, Jingxin; Rasool, Nouman; Li, Kang; Zhu, Huacheng; Yang, Yang
Abstract: Three-stub waveguides are common impedance matching devices which are essential for a wide range of high-power microwave applications. Based on equivalent circuit analysis method, this article presents a novel matching algorithm which can be applied for three-stub tuners to implement continuous, automatic and real-time impedance matching. Equivalent model of a stub waveguide is firstly established by using transmission lines in series and capacitors in parallel. Then, according to the proposed model, the mathematical expression of reflection coefficient at different stub depth is derived by using currently detected reflection coefficient and stub depth. Later, based on the derived expression, an algorithm is developed to determine the optimum insertion depths of the stubs when VSWR is minimum. The S 11 parameters of the stub waveguide which are calculated by the method agree well with those measured by vector network analyser. Meanwhile, the algorithm is able to limit reflection coefficient under –10 dB and can easily be redesigned for waveguides of different sizes. Thus, it shows a promising future in industrial impedance matching applications.